Cleft Care of Internationally Adopted Children From China. (January 2019) - Kaye, Alison; Che, Columbine; Chew, William L.; Stueve, Elizabeth A.; Jiang, Shao
Objective: To quantify a population of international adoptees from China with cleft lip and/or palate to assess presentations and team management practices. Design: Single institution retrospective. Patients: One hundred one patients with cleft lip and/or palate and history of international adoption from China. Results: Forty-nine males and 52 females were adopted from 2001 to 2014. Median age at arrival was 26 months. A total of 88.1% had a combined cleft lip and palate: 59 unilateral, 30 bilateral. Only 4 patients had isolated cleft palate. A total of 85.6% had cleft lip repair before adoption; 41.6% had both cleft lip and palate repairs in China. A total of 14.9% of adoptees had no prior surgery. In China, median age at lip repair was 10 months, and palate repair was 19 months. Once in the United States, lip repair was at 24 months and palate repair at 24 months. Eighty-three revision surgeries were performed. A total of 79.2% of children demonstrated moderate to severe articulation disorders. A total of 36.6% had velopharyngeal insufficiency with hypernasal speech. Forty percent required palatal revision surgery to achieve normal resonance. Fifty seven percent of patients presented with concomitant medical issues but less than 10% with global delays or autism. Conclusions: Chinese adoptees have more complex presentations and delayed surgical care compared to their domestic counterparts. Engaging prospective families starting before adoption helps to manage expectations. Long-range planning, timely surgery, aggressive therapy, and close careful follow-up can mitigate some of these differences. Speech and language problems including articulation disorders, expressive delays, and hypernasality are frequent and can persist despite interventions.